Entomophthoramycosis by Conidiobolus coronatus. Report of a case successfully treated with the combination of itraconazole and fluconazole - Antonio Carlos Francesconi do VALLE; Bodo WANKE; Márcia dos Santos LAZÉRA; Paulo Cezar Fialho MONTEIRO; Maria de Lourdes VIEGAS (Universidade de São Paulo (USP), 2001)
Rhinoentomophthoramycosis caused by Conidiobolus coronatus in a 61-year old woman was unsuccessfully treated during 8 years with all the antifungals available in the Brazilian market, including potassium iodide for 1 month, sulfamethoxazole plus trimethoprim for 2 months, amphotericin B, total dose of 1130 mg, cetoconazole, 400 mg/day for 6 months, fluconazole, 200 mg/day, for at least 2 months and, itraconazole, 400 mg/day for 2 months, followed by 200 mg/day for 4 more months. Complete clinical and mycological cure was achieved using itraconazol 400 mg/day in association with fluconazol 200 mg/day during 24 months. After cure she was submitted to plastic surgery to repair her facial deformation. Today she remains clinically and mycologically cured after 59/60 months (5 years!) without any specific antifungal. We thus suggest the use of the combination of itraconazole and fluconazole as an additional option for the treatment of this mycosis.